The effect of design-based STEM learning on students' scientific creativity in solar energy topic - Lidya, Nala; Habibah, Hulwah; Suryadi, Ahmad (Universitas PGRI Kanjuruhan Malang, 2024)
This study aims to investigate the effect of design-based STEM learning on students' scientific creativity in the context of solar energy. The study involved 64 tenth-grade students from a public Madrasah Aliyah in Jakarta, who were split into two groups: an experimental group that used design-based STEM learning and a control group that used conventional learning. Both groups were given a scientific creativity posttest in the form of seven open-ended questions. The study results showed that the experimental group's average scientific creativity score was higher than the control group's. Furthermore, the subdimensions analysis revealed that the experimental group's flexibility and originality significantly affected their scientific creativity. The study shows that design-based STEM learning positively impacts students' scientific creativity in the context of solar energy, although with a low category. This research can be a reference for future research to investigate the influence of design-based STEM learning on students' scientific creativity in various contexts.